A case of high altitude cutaneous leishmaniasis in a non-endemic region in Nepal. (February 2020) - Bastola, Anup; Shrestha, Mitesh; Lamsal, Mahesh; Shrestha, Srijan; Prajapati, Sabita; Adhikari, Anurag; Gupta, Birendra Prasad; Hide, Mallorie; Devkota, Lina; Chalise, Bimal Sharma; Pandey, Kishor; Manandhar, Krishna Das
Abstract: A case of cutaneous leishmaniasis was discovered in a 32-year old man with a persistent erythematous plaque. The patient resides in a high altitude ( 2000 m above sea level) area that is not endemic for cutaneous leishmaniasis in the Dunai village of Dolpa, Nepal. The patient's lesion was initially misdiagnosed as lupus vulgaris. After response failure to initial treatment, additional testing by histological microscopy revealed the presence of Leishmania amastigotes in tissue from the lesion, and the diagnosis of cutaneous leishmaniasis was confirmed by nested PCR DNA assay of tissue from the lesion, and by a positive rK39 test in blood. Sequencing of the kinetoplast region confirmed the presence of Leishmania donovani complex. The patient responded well to treatments for cutaneous leishmaniasis and the skin lesions regressed after 6 months. This is the first known case of cutaneous leishmaniasis in a patient in Nepal who resides at high altitude in a non-endemic region. Increasing temperatures in this region of Nepal may be expanding the range of vectors that transmit cutaneous leishmaniasis. Graphical abstract: Unlabelled Image